Antagonism of vitamin C and vitamin E on action of quinolones - Julius E. Surdjawidjaja (Faculty of Medicine, Universitas Trisakti, 2012)
The quinolone antibiotics are potent drugs for combating infections caused by various bacterial species with satisfactory results and relatively minimal adverse effects. Antioxidant dietary supplements, such as vitamin C (ascorbic acid) and vitamin E (a-tocopherol), are occasionally prescribed along with quinolone antibiotics during the course of treatment of an infection. Therefore it is important to understand the effects of these antioxidants on the antibacterial action of quinolone antibiotics.